The Media Literacy Level Of Slovak Seniors - Petranová, Dana (Communication Today, 2025)
The paper offers a summary of main findings of the quantitative research on the media literacy level of Slovak seniors. We have conducted our research within a broader set of research activities of IMEC – International Media Education Centre founded thanks to initiative by Faculty of Mass Media Communication, University of SS. Cyril and Methodius in Trnava. The research was focused on mapping the media competencies of Slovak senior population. The main goal was to find out the level of media literacy of our seniors. To what extent are they able to use computers and the Internet? Are the ways they use media active and balanced or not? Do they understand media content and its functions? What is their knowledge about media regulation? We also paid attention to the issue of seniors using media for public participation as well as to their skills related to creating media contents. Our findings suggest that Slovak seniors reach the basic level of media literacy in all three considered categories: user competencies, critical thinking and communication skills. Therefore, we are able to confirm that the seniors are aware of the basic media functions and they know how to use media for education purposes, relax or entertainment.